2009
DOI: 10.3390/s90604446
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Acoustic Sensors Based on Fiber Bragg Gratings

Abstract: We report on recent results obtained with a fiber optic hydrophone based on the intensity modulation of the laser light in a FBG (Fiber Bragg Grating) under the influence of the sound pressure. In order to control the behavior of the hydrophone in terms of sensitivity and bandwidth, FBGs have been coated with proper materials, characterized by different elastic modulus and shapes. In particular, new experiments have been carried out using a cylindrical geometry with two different coating, showing that the sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 9 publications
2
20
0
Order By: Relevance
“…To this aim, a tunable laser was used to lock the operating wavelength on the linear edge of the grating response. Since spectrum of FBG shifts without changing its shape [3,[6][7], the change in reflection at the laser wavelength is also expected to be proportional to pressure. The optoelectronic setup thus consists in a stable tuneable laser (Yokogawa AQ2200-136), a 2x1 coupler capable to split transmitted and reflected signals whereas a photodiode provides an electrical output proportional to the optical power of the laser reflected from the grating edge.…”
Section: Sensor Fabrication and Methodologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…To this aim, a tunable laser was used to lock the operating wavelength on the linear edge of the grating response. Since spectrum of FBG shifts without changing its shape [3,[6][7], the change in reflection at the laser wavelength is also expected to be proportional to pressure. The optoelectronic setup thus consists in a stable tuneable laser (Yokogawa AQ2200-136), a 2x1 coupler capable to split transmitted and reflected signals whereas a photodiode provides an electrical output proportional to the optical power of the laser reflected from the grating edge.…”
Section: Sensor Fabrication and Methodologiesmentioning
confidence: 99%
“…Finally, when the coating size approaches the acoustic wavelength, a decrease in the sensitivity is observed that can be attributed to acoustic diffraction. In order to validate the numerical results, here, we report the experimental analysis of the acoustic performance of cylindrically coated FBG hydrophones with different diameters in an extended frequency range (4Khz-35Khz) compared with our previous work [6][7]. In particular, here we focused the attention on two sensors with height fixed to 30mm and coating diameter of 5 mm and 10 mm, respectively (here named 5-30 and 10-30 respectively).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies measure 3 pm of shifts in the Bragg wavelength when a pressure of 1 MPa is applied on a bare FBG sensor [5]. This prevents the FBG sensors from large deformation under acoustic pressure [6]. This eventually results in the low sensitivity of the FBG-based sensors in their use in underwater applications.…”
Section: Introductionmentioning
confidence: 99%
“…The most significant performance is their immunity to electromagnetic interference, which enables applications under harsh environment [4]. In recent years, FBG has become an attractive candidate for ultrasonic wave detection, because it can be easily embedded in the structure of the body being monitored and is ideal for multiplexing [5,6].…”
Section: Introductionmentioning
confidence: 99%